Analisis Metode Qiyas Imam Syafi’i - Lutfi Zarkasi; Raffi, Achmad (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2023)
Ushul fiqh is a very important science in producing Islamic law that is responsive and adaptable to contemporary problems, because it is a science that contains a collection of methods, basics, approaches and theories used in understanding Islamic teachings. This research was conducted using the library research method, which involves taking and collecting data from various literature sources that are relevant to the problem being researched. The majority of ulama agree that qiyas is a form of proof or argument that comes from the Al-Quran and Sunnah to determine the law regarding a case that has not been regulated in the main text. However, there are views that do not agree with the qiyas method, as expressed by Abu Zaid and Fazlur Rahman. They argue that qiyas is an imperfect and less convincing form of analogy, because it assumes ambiguity in the Al-Quran and Sunnah, so it requires explanation through the process of analogy. Criticism of As-Shafi'i epistemology by Al-Jabiri highlights the use of bayani thinking in understanding texts, with language as the main tool. Nevertheless, As-Syafi'i's contribution in developing ulus al-fiqh had a spectacular impact.